2006
DOI: 10.1158/1541-7786.mcr-05-0229
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Demethylation and Histone Acetylation Mediate Gene Expression of MAGE-A1, -A2, -A3, and -A12 in Human Cancer Cells

Abstract: The broad range of expression of cancer-testis antigens in various tumor types makes the proteins encoded by human MAGE gene family promising targets for anticancer immunotherapy. However, a major drawback is their heterogeneous expression. In the current study, we have examined the influence of the DNA methylase inhibitor 5-aza-2 ¶-deoxycytidine (5-aza-CdR) together with the histone deacetylase inhibitor trichostatin A on the expression of MAGE-A1, -A2, -A3, and -A12 genes in different cell lines. Reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
126
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 34 publications
17
126
0
Order By: Relevance
“…No difference in overall survival was found, but the median follow-up of these patients' series was too short to conclude that point. This is in agreement with recent findings in other cancers showing that CT-X gene expression is often coordinated due to hypomethylation of their promoters (50,51). In addition, CT-X gene expression in patients with epithelial cancers is often associated with a poor patient outcome (52)(53)(54).…”
Section: Discussionsupporting
confidence: 92%
“…No difference in overall survival was found, but the median follow-up of these patients' series was too short to conclude that point. This is in agreement with recent findings in other cancers showing that CT-X gene expression is often coordinated due to hypomethylation of their promoters (50,51). In addition, CT-X gene expression in patients with epithelial cancers is often associated with a poor patient outcome (52)(53)(54).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies (Weber et al, 1994;Sigalotti et al, 2004;Wischnewski et al, 2006) have shown that epigenetic manipulation could enhance TAA expression including MAGE family, which is based on these TAA genes commonly with hypermethylated CpG sites in promoter region. Here, we report at the first time the methylation status of MAGED4.…”
Section: Discussionmentioning
confidence: 99%
“…MAGE is a large gene family, in which some genes encode tumor-associated antigens with characteristics of broad expression in various tumors but restricted in normal tissues, and recognizing by cytotoxic T lymphocytes (CTLs) (Inoue et al, 1995;Wischnewski et al, 2006). Some of MAGE antigens and their epitope peptides constitute important targets for antitumor immunotherapy with a number of clinical studies already completed or underway (Duffour et al, 1999;Rosenberg et al, 2004;Morse et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of several CTA has been linked to DNA hypomethylation [15,20,21]. We, therefore, investigated whether epigenetic treatment might increase the comparably infrequent CTA expression in AML cells.…”
Section: Demethylation But Not Inhibition Of Histone Deacetylation Inmentioning
confidence: 99%